Chiral single-photon generators - Chen, Disheng (2021)
Chiral photons have the potential to advance information technologies due to their robustness in carrying binary data against noisy backgrounds as well as their capacity for constructing single-photon isolators and circulators through nonreciprocal photon propagation. In this Perspective, we highlight recent efforts to generate chiral single photons using circularly polarized light sources. We delve into possible future technologies that integrate these light sources with other active optical elements as a versatile platform for information processing.